Penilaian Kondisi Terumbu Karang Di Area Perairan Dangkal Tanjung Pantai Senggigi, Lombok Barat, Nusa Tenggara Barat - Himawan, Mahardika Rizqi; Hariadi, Muhammad Dipa; Pratama, Alfian; Lestariningsih, Wiwid Andriyani (LPPM Universitas Mataram, 2025)
This study aims to assess the condition of coral reefs based on benthic composition in the shallow waters of Tanjung, Senggigi Beach, West Lombok, West Nusa Tenggara. Data collection was carried out through diving using the Underwater Photo Transect (UPT) method by analyzing 50 quadrat photos taken along a 50-meter transect line, processed with the CPCe software. The analysis revealed that live coral (Coral) was the most dominant benthic component, with an average cover of 91.38% Â± 13.72%, which falls under the